Trace amine-associated receptors as potential targets for the treatment of anxiety and depression - Li, Zelong; Wan, Luoting; Dong, Jing; Li, Jinquan; Liu, Jianfeng (Frontiers in Pharmacology, 2025)
In the metabolic pathways associated with major biogenic amines, such as dopamine, noradrenaline, and serotonin, there exists a group of compounds known as trace amines. These trace amines share structural similarities with the major biogenic amines. Since the discovery of trace amine-associated receptors (TAARs) that are activated by trace amines, numerous studies have suggested that these receptors, particularly the TAAR1 subfamily, play a role in modulating the stress response and are involved in stress-related psychiatric disorders, including depression, bipolar disorder, and anxiety. Research indicates that TAAR1 regulates the release of neurotransmitters like dopamine and serotonin, which may be a potential mechanism underlying the involvement of trace amines and TAAR1 in response to stress. Several selective TAAR1 agonists have been evaluated in various animal models of depression and anxiety, showing that these compounds can be effective in alleviating depressive and anxiety-like behaviors. Additionally, TAAR5 has also been found to have an effect on anxiety; it is proposed that a TAAR5 antagonist might produce anxiolytic effects. Despite our limited understanding of the underlying mechanisms through which TAARs regulates stress-related disorders, current evidence strongly suggests that TAAR ligands could represent novel pharmacotherapy for treating psychiatric disorders such as depression, bipolar disorder, and anxiety disorders like post-traumatic stress disorder (PTSD). This offers hope for more effective and safer treatment options in the field of mental health.